Inequality and the import demand function - Antonis Adam; Margarita Katsimi; Thomas Moutos (Center for Economic Studies and ifo Institute (CESifo), 2008)
In this paper we build a model of trade in vertically differentiated products and find that income inequality can affect the demand for imports even in the presence of homothetic preferences. The empirical importance of changes in inequality on the demand for imports is then assessed by examining panel data for 36 developing and developed countries for the 1980-1997 period. We find significant evidence supporting our prediction that inequality has a large influence on the demand for imports. Moreover we find that, in line with the predictions of our theoretical model, this influence is positive for high-income countries (countries that produce the high quality variety of the vertically differentiated product) and negative for low-income countries (countries that produce the low quality variety of the vertically differentiated product).
Keywords: F13; H23; O24; 330; inequality; import demand; vertically differentiated products; panel data; Importnachfrage; Verteilungsgerechtigkeit; Schätzung; Panel; Entwicklungsländer; Industriestaaten; Welt